Two-eyed seeing, arts-based reflection and collaboration: Reflexivity tools for nursing practitioners working across cultures - Kuhnke, Janet Lynne; Jack-Malik, Sandra (European Journal for Qualitative Research in Psychotherapy, 2019)
This paper explores how the use of reflexivity, an approach to knowledge construction and understanding, provided a structural framework for a doctoral student of psychology as she conducted a literature review and worked as a registered nurse in clinical practice. Her reflexive practice allowed for the exploration of perspectives, biases, values and knowledge system and therefore it added rigour, credibility and trustworthiness to both her literature review and clinical work. Although Janet is not a psychotherapist, her reflexive practice shaped the relationships she developed and influenced the care she provided to people living with diabetic foot ulcers because her therapeutic and community involvement overlapped. Janet’s reflexive practice helped her move beyond the delivery of physical wound care towards more inclusive and expansive relationships with individuals, communities, doctors, psychologists, and family members. As these collaborative and inclusive relationships developed, questions about struggles and socio-cultural knowing influenced her understandings and pushed at what she imagined holistic and culturally relevant care might involve. Because her clinical work was geographically located within Aboriginal communities, her reflexive practice was also informed by the principles of Two-Eyed Seeing. Writing, journaling, listening, conversations and creating ‘art-as-event’ are the strategies which serve as a resource for this paper. In addition, it is important to note this reflexive writing is collaborative and multi-disciplined (nursing, psychology, and education). Our collaboration resulted in opportunities to understand, challenge and value other perspectives born and experienced on landscapes unfamiliar to us as individuals, professionals and women working in communities.